Isorhamnetin and its new derivatives isolated from sea buckthorn berries prevent H2O2/Fe – Induced oxidative stress and changes in hemostasis. (March 2019) - Skalski, Bartosz; Lis, Bernadetta; Pecio, Łukasz; Kontek, Bogdan; Olas, Beata; Żuchowski, Jerzy; Stochmal, Anna
Abstract: The objective of this study is to investigate the biological effects of phenolic compounds extracted from the sea buckthorn berries on oxidative stress and hemostasis. The sea buckthorn ( Elaeagnus rhamnoides (L.) A. Nelson) berries are rich in flavonoids and non-polar compounds. In this study, the activity of the phenolic fraction from the sea buckthorn berries was evaluated in vitro in comparison with three phenolic compounds: isorhamnetin (compound 1) and its two new derivatives: compound 2 (isorhamnetin 3- O -beta-glucoside-7- O -alfa-rhamnoside) and compound 3 (isorhamnetin 3- O -beta-glucoside-7- O -alfa-(3"'-isovaleryl)-rhamnoside). The impact of these phenolic compounds and the phenolic fraction against the effect of the donor of hydroxyl radicals - H2 O2 /Fe on proteins and lipids in human plasma was measured. Additionally, the aim of the study was to determine the effect of these phenolic compounds and the phenolic fraction on various typical hemostasis parameters. Our results show that the used derivatives of isorhamnetin possess different biological properties (e.g. antioxidant, anti-platelet and anticoagulant). The tested compounds can be seen as new natural beneficial compounds to be used in prevention and treatment of cardiovascular diseases. Graphical abstract: Image 1 Highlights: Isorhamnetin and its two derivatives reduce the lipid peroxidation and protein carbonylation in human plasma. The isorhamnetin derivative (compound 3) extends the thrombin time. Isorhamnetin and its derivative (compund 3) inhibit aggregation induced by thrombin. Derivatives of isorhamnetin can be new natural compounds possessing antioxidant, anti-platelet and anticoagulant activities.